(untitled) (Research, Society and Development, 2021)
Objective: To identify the knowledge of undergraduate students in the health area about Basic Life Support in cardiorespiratory arrest. Methodology: This is a descriptive study with a quantitative approach, carried out between the months of September and October 2020 and with the participation of 194 students from the Nursing, Physiotherapy, Nutrition and Psychology courses of a public university in the State of Large northern river. The collection was performed by google forms through a questionnaire prepared by the authors based on the basic life support protocol of the American Heart Association. The study was approved by the research ethics committee, under opinion Nº. 4,018,759. Results: Based on the 194 students who answered the 8 specific questions, a total of 1,552 (100%) answers were obtained, of which 475 (30.6%) were correct, 434 (27.9%) were wrong and 643 (41, 4) did not know how to answer. Conclusion: The findings showed a deficit in the knowledge of students in the health area about basic life support, identifying the need for activities in undergraduate courses that address this theme.